GAMBARAN POLA TIDUR IBU NIFAS - Rizka Fatmawati; Nur Hidayah (Universitas Duta Bangsa Surakarta, 2019)
Sleep is one of the basic human needs that can be influenced by various factors that will affect the disruption of sleep fulfillment in a person. Lack of rest or sleep in postpartum mothers will result in lack of milk supply, slow the process of uterine involution, and cause the inability to care for babies and depression. The research design used was descriptive survey method. The subjects of the study were postpartum mothers in the area of ​​Puskesmas nusukan, Banjarsari, Surakarta. The study was conducted during July-August 2019. The sample technique used simple random sampling with a sample of postpartum mothers with a total of 21 respondents. The results of the postpartum mother's sleep patterns, postpartum mother's naps at the most 120 minutes a day, while the longest night's sleep 520 minutes a day.